Validity and reliability of the Dynamic Gait Index in children with hemiplegic cerebral palsy - KARADAĞ SAYGI, NAİME EVRİM (ELSEVIER IRELAND LTD, 2020)
Background: Dynamic Gait Index (DGI) is a performance-based tool can be applied in a short time and evaluates dynamic balance and gait ability. Research question: Is the DGI valid and reliable for assessing gait and balance disorders in children with hemiplegic cerebral palsy (CP)? Methods: Sixteen children with hemiplegic CP (5 females, 11 males; mean age 10y 3mo, SD 2y 7mo; range 6-14y; Gross Motor Function Classification System (GMFCS) levels I [n = 9], II [n = 7]) and 16 age-matched typically developing (TD) (8 females, 8 males; mean age 9y 9mo, SD 2y 6mo; range 6-14y) participated. The relationship between the DGI, Four-Square Step Test (FSST), Timed Up and Go Test (TUG) and Pediatric Berg Balance Scale (PBS) was analyzed. To determine the test-retest reliability, the DGI was performed twice and; for the inter-rater reliability, only DGI was reapplied by a different rater on the same day. Internal consistency was obtained by Cronbach-a value. Validity was tested by Spearman correlation coefficient and reliability was calculated by Intraclass correlation coefficient (ICC). Results: There was a significant difference between hemiplegic CP and TD and between the children with GMFCS level I and II in the comparison of results of the DGI and other tests. All items on the DGI had appropriate internal consistency (Cronbach-a= 0.969). The test-retest (ICC= 0.970 CI(0.915- 0.990)) and inter-rater (ICC= 0.983 CI(0.882- 0.998)) reliabilities were found to be excellent. A negative, moderate correlation between FSST and DGI (rs= -0.673, p= 0.004); a positive, high correlation between PBS (rs= 0.724, p= 0.002) and DGI and a negative, high correlation between TUG and DGI (rs=-0.828, p < 0.001) was detected. Significance: DGI with features such as its feasibility in a short time, being simple but distinctive and not requiring heavy equipment is a valid and reliable method in children with hemiplegic CP.
Keywords: Balance; Cerebral palsy; Dynamic Gait Index; Gait; Postural control; Validity and reliability; SQUARE STEP TEST; LOWER-EXTREMITY; GO TEST; STABILITY; SCALES